Associations of edge detected and manual traced common carotid intima-media thickness (IMT) measurements with Framingham risk factors: the Multi-Ethnic Study of Atherosclerosis - Polak, Joseph F. (2011)
BACKGROUND: Carotid intima-media thickness (IMT) is a marker of cardiovascular disease derived from ultrasound images of the carotid artery. In most outcome studies, human readers identify and trace the key IMT interfaces. We evaluate an alternate approach using automated edge detection. METHODS: We study a subset of 5640 participants with an average age 61.7 years (48% men) of the Multi-Ethnic Study of Atherosclerosis composed of whites, Chinese, Hispanic and African-Americans that are part of the MESA IMT progression study. Manual tracing IMT (mt_IMT) and edge-detected IMT (ed_IMT) measurements of the far wall of the common carotid artery (CCA) served as outcome variables for multivariable linear regression models using Framingham cardiovascular risk factors and ethnicity as independent predictors. RESULTS: Measurements of mt_IMT was obtainable in 99.9% (5633/5640) and of ed_IMT in 98.9% (5579/5640) of individuals. Average ed_IMT was 0.19 mm larger than mt_IMT. Inter-reader systematic differences (bias) in IMT measurements were apparent for mt_IMT but not ed_IMT. Based on complete data on 5538 individuals, associations of IMT with risk factors were stronger (p < 0.0001) for mt_IMT (model r(2:) 19.5%) than ed_IMT (model r(2:) 18.5%). CONCLUSION: We conclude that this edge-detection process generates IMT values equivalent to manually traced ones since it preserves key associations with cardiovascular risk factors. It also decreases inter-reader bias, potentially making it applicable for use in cardiovascular risk assessment.